Implementasi Metode Data Encryption Standard (Des) Untuk Enkripsi Dan Dekripsi Data Kependudukan Desa Wonoharjo - tri agustina; Suhirman Suhirman (Program Studi Informatika Universitas PGRI Yogyakarta, 2025)
Wonoharjo Village is one of the villages in Kemusu sub-district, Boyolali district, Central Java province with a population of 3,208 people. The population data is currently only stored in the village computer folder which can be accessed by anyone and without any special security to secure the data. This is certainly very risky if there are irresponsible people accessing the computer and misusing population data for personal gain. To overcome these problems, a system was created that uses the Data Encryption Standard (DES) algorithm as a method to secure resident data. Data security is done through an encryption process using a symmetric key when resident data is added to the system. Based on the results of the research that has been done, the resident data is successfully encrypted properly in the database with a ciphertext form that is difficult to understand. So it can be concluded that the system created can secure resident data from data leakage and misuse compared to the previous system.